2019
DOI: 10.1111/nph.15986
|View full text |Cite
|
Sign up to set email alerts
|

A unified framework for plant life‐history strategies shaped by fire and herbivory

Abstract: Fire and herbivory both remove aboveground biomass. Environmental factors determine the type and intensity of these consumers globally, but the traits of plants can also alter their propensity to burn and the degree to which they are eaten. To understand plant life-history strategies associated with fire and herbivory we need to describe both response and effect functional traits, and how they sort within communities, along resource gradients, and across evolutionary timescales. Fire and herbivore functional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
114
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(115 citation statements)
references
References 95 publications
1
114
0
Order By: Relevance
“…We interpret these species as being potentially able to persist in communities shaped either by fire or grazing through tolerating both consumers to some degree. These species, such as Hyparrhenia rufa, Heteropogon contortus and Sporobolus pyramidalis, also have pan-African or even cosmopolitan range sizes as would be expected if a species can tolerate a wide range of disturbance conditions [57]. In our dataset, these species were functionally clustered within the fire grasses, but possibly as a product of traits being sampled where species were first encountered in our surveys, i.e.…”
Section: Discussionmentioning
confidence: 74%
“…We interpret these species as being potentially able to persist in communities shaped either by fire or grazing through tolerating both consumers to some degree. These species, such as Hyparrhenia rufa, Heteropogon contortus and Sporobolus pyramidalis, also have pan-African or even cosmopolitan range sizes as would be expected if a species can tolerate a wide range of disturbance conditions [57]. In our dataset, these species were functionally clustered within the fire grasses, but possibly as a product of traits being sampled where species were first encountered in our surveys, i.e.…”
Section: Discussionmentioning
confidence: 74%
“…Spatial differences in plant species distributions, and associated plant traits, have been shown to influence both fire regime characteristics [14] and post-fire ecosystem properties [15]. Traditional plant functional traits such as seed size, leaf thickness, and growth rate are also important for determining flammability and post-fire recovery [16][17][18]. Recently, a suite of plant traits have been identified that indicate fire adaptations or co-evolution with fire [14,18].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional plant functional traits such as seed size, leaf thickness, and growth rate are also important for determining flammability and post-fire recovery [16][17][18]. Recently, a suite of plant traits have been identified that indicate fire adaptations or co-evolution with fire [14,18]. These traits, such as bark thickness, seed dispersal distance, and serotiny, vary in subalpine forests of the western US.…”
Section: Introductionmentioning
confidence: 99%
“…In savannas, a clear functional distinction can be made between 'lawn grasses' and 'bunch grasses', where lawn grasses are characterized by traits that enable plants to withstand both grazing and drought (Coughenour 1985, Veldhuis et al 2014. Examples of traits associated to lawn grasses include basal tillering, elongated rhizomes, and extravaginal branching (Archibald et al 2019). Overall lateral growth-form is adaptive against grazing because leaf material is kept close to the soil, reducing accessibility to herbivores and because stronger root networks associated to mat-forming grasses prevent uprooting (Archibald et al 2019).…”
Section: Chaptermentioning
confidence: 99%
“…Examples of traits associated to lawn grasses include basal tillering, elongated rhizomes, and extravaginal branching (Archibald et al 2019). Overall lateral growth-form is adaptive against grazing because leaf material is kept close to the soil, reducing accessibility to herbivores and because stronger root networks associated to mat-forming grasses prevent uprooting (Archibald et al 2019). At the same time, rhizomatous clonal grasses store carbohydrates, nutrients and water in rhizomes (Bai et al 2010) which may improve resistance to drought.…”
Section: Chaptermentioning
confidence: 99%